Does the Dexamethasone Suppression Test Reliably Discriminate Between Psychotic and Nonpsychotic Major Depression? An Exploratory Analysis of Potential Confounds - Gaudiano, Brandon A. (2009)
Previous research has shown that psychotic major depression (PMD) is often associated with higher rates of nonsuppression on the dexamethasone suppression test (DST) compared with nonpsychotic major depression (NMD), suggesting the potential importance of cortisol hypersecretion in the psychotic subtype of the disorder. However, these patient groups also are known to differ from one another on a variety of other clinical variables, and there are numerous factors independent of diagnostic status known to affect the DST. Thus, we investigated possible confounds that could help account for the apparent DST abnormalities in PMD sometimes reported in past research. Hospitalized patients with PMD (n = 11) and NMD (n = 58) were compared on the DST and other clinical variables. As expected, PMD patients showed significantly higher rates of DST nonsuppression (55% vs 24%; p = .04). However, PMD patients also had significantly higher levels of anxiety severity (p = .01). The higher rates of nonsuppression in the PMD group were attenuated when these patients were compared with a subsample of NMD patients matched on anxiety severity (55% vs 55%). Implications for future research on biological markers of PMD are discussed.